This question is with respect to Theorem 7.1 of Mallat's Wavelet Tour text. It is a follow-up of sorts to a previous question.


Suppose I have a set $\{\theta(t-n)\}_{n \in \mathbb{Z}}$ which is a Riesz basis for a space $V \subset L^2(\mathbb{R})$. For some $\varphi \in V$, I can thus expand:

$$ \varphi(t) = \sum_{n\in \mathbb{Z}} a_n \theta(t-n) $$


$$ \hat{\varphi}(w) = \hat{a}(w)\hat{\theta}(w) $$ where $\hat{f}$ denotes the Fourier transform of $f$, and $\hat{a}(w) = \sum_n a_n e^{-iwn}$.

By letting $$ \hat{a}(w) = \left( \sum_{k \in \mathbb{Z}} |\hat{\theta}(w+2\pi k)|^2 \right)^{-1/2} $$

we actually determine a $\varphi$ such that

$$\langle \varphi(t-m), \varphi(t-n) \rangle = \delta[m-n] \tag{1}$$

That is, integer translates of $\varphi$ form an orthonormal set on $V$. This follows since condition $(1)$ is equivalent to

$$\sum_k |\hat{\varphi}(w+2\pi k)|^2 = 1$$


It is said that this orthonormal set also forms an orthonormal basis for the space $V$, but I can't seem to see why this should be the case. Here is my reasoning:

Suppose we have some arbitrary $f \in V$. Then: $$ f(t) = \sum_{n\in \mathbb{Z}} b_n \theta(t-n) $$ and $\hat{f}(w) = \hat{b}(w) \hat{\theta}(w)$ where $\hat{b}(w) = \sum_n b_n e^{-iwn}$.

Now set $$ g(t) = \sum_{n \in \mathbb{Z}} \langle f(t), \varphi(t-n)\rangle \varphi(t-n) = \sum_{n \in \mathbb{Z}} c_n \varphi(t-n) $$ where we have $\hat{g}(w) = \hat{c}(w)\hat{\varphi}(w)$ with $\hat{c}(w) = \sum_n c_n e^{-iwn}$.

If $\{\varphi(t-n)\}_{n \in \mathbb{Z}}$ is indeed a basis, it should follow that $\hat{f}(w) = \hat{g}(w)$ (and hence $f(t)=g(t)$) or

$$\hat{b}(w) = \hat{c}(w) \hat{a}(w)$$

since $\hat{\varphi}(w) = \hat{a}(w)\hat{\theta}(w)$. My problem is that I can't seem to verify this equality! Is there a more obvious way to show this?


I will expand on Chris's answer below.

Suppose we found coefficients, $b_n$, such that $\theta = \sum_n b_n \varphi_n$. Then

$$ \theta_n = \sum_m b_m \varphi_{m+n} = \sum_m b_{m-n} \varphi_m $$

so that $$ f\in V \Rightarrow f = \sum_n c_n \theta_n = \sum_n \sum_m c_n b_{m-n} \varphi_m $$

We'd like to show these coefficients, $b_n$ exist and that $||\theta - \sum_nb_n\varphi_n||^2 = 0$

Now, $$ ||\theta - \sum_nb_n\varphi_n|| = \frac{1}{2\pi} ||\hat{\theta} - \hat{b}\hat{\varphi}|| = \frac{1}{2\pi} ||\hat{\theta} (1 - \hat{b}\hat{a})|| $$

Consider letting $b_n = \langle \theta, \varphi_n \rangle$. Or rather,

$$ b[n] = (\theta * \tilde{\varphi})[n] $$

where $\tilde{\varphi} = \varphi(-t)^*$ (time reversed conjugate). So then

\begin{align} \hat{b}(w) &= \sum_k \hat{\theta}(w + 2\pi k) \varphi(w + 2\pi k)^* \\ &= \sum_k \hat{\theta}(w + 2\pi k) \theta(w + 2\pi k)^* \hat{a}(w+2 \pi k)^* \\ &= \hat{a}(w) \sum_k |\hat{\theta}(w + 2\pi k)|^2 \\ & = \frac{1}{\hat{a}(w)} \end{align}

So that $||\hat{\theta} (1 - \hat{b}\hat{a})|| = 0$ ( the second to last line owing to the fact that $\hat{a}(w)$ is real and $2\pi$ periodic by definition ).


We know that the family $\{T_k\theta\}_{k\in \mathbb Z}$ spans $V$. Therefore, if we can write any of the functions in in this family as a superposition of the functions $\{T_n\varphi\}_{k\in \mathbb Z}$ we can conclude that this family also spans $V$. Therefore we need to find $b_{n,k}$, such that $$ \theta(t-k) = \sum_{n \in \mathbb Z} b_{n,k} \varphi(t-n). \tag{1} $$ Looking at Equation (1) we see through an index shift that it suffices to find $b_{n, 0}$. Taking Fourier transforms we need to construct the sequence, such that $$ \hat \theta(\omega) = \hat b(\omega) \hat \varphi(\omega). \tag{2} $$ Using your formulas from above we see that $\hat b(\omega) = 1/\hat a(\omega)$. So we can inverse Fourier transform Equation (2) to actually get the sequence $b_n$. I have not thought about convergence of all the involved transforms but that should be the correct rationale...

  • $\begingroup$ Thanks, I've added a follow up using your idea. Something still feels a little...funny, but I think you are right that this is the basic gist of it. $\endgroup$
    – Chester
    Feb 27 '15 at 20:04
  • $\begingroup$ I am glad that you could follow the reasoning behind my answer... it was quite confusing, I was in a bit of a rush when I wrote it. I did some editing to improve it a bit. I hope your funny feeling will subside at a certain point because I think the resoning is true. ;) $\endgroup$
    – Chris
    Mar 2 '15 at 8:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.